2014
DOI: 10.7860/jcdr/2014/7803.4863
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidative and Antidiabetic Activity of Bark of Holarrhena Pubescens Wall

Abstract: Objective: The objectives of the study are to screen out various phytochemicals and to evaluate the antioxidant and antidiabetic potential of the stem bark of Holarrhena pubescens Wall (Holarrhena antidysenterica). Materials and Methods:The antioxidant activity was determined by the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging activity where ascorbic acid was taken as positive control. The antioxidant property was later exploited and the methanolic extract of plant was tested for antihyperglycemic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 9 publications
3
25
0
Order By: Relevance
“…Methanol extract of A. indica has shown the highest activity followed by its chloroform extract which coincide with the previous study (Sri et al, 2012). The antioxidant activity shown by methanol extract was much higher than that of chloroform extract which may be due to the presence of polar compounds like phenols, flavonoids, etc., that are soluble in methanol (Bhusal et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Methanol extract of A. indica has shown the highest activity followed by its chloroform extract which coincide with the previous study (Sri et al, 2012). The antioxidant activity shown by methanol extract was much higher than that of chloroform extract which may be due to the presence of polar compounds like phenols, flavonoids, etc., that are soluble in methanol (Bhusal et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the chemistry and the biological activity studies in genus Holarrhena, H. antidysenterica has been thoroughly investigated. These studies revealed that its bark, leaves and seeds showed anti-diabetic, antioxidant (Ali et al, 2009;Bhusal et al, 2014;Ganapathy et al, 2011;Hegde and Jaisal, 2014;Korpenwar, 2011;Preethi et al, 2010;Ray, 2014;Sabira et al, 2014;), antibacterial and antifungal activities (Ballal et al, 2001;Preethi et al, 2010;Rath and Padhy, 2014). In addition, seeds have acetylcholinesterase inhibitory activity which is useful for treating neurological disorders (Yang et al, 2012) and has diabetic defense as well as the ability to reduce triglycerides which affect the total cholesterol level (Pathak et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant Activity. The DPPH radical-scavenging method was used to quantify the antioxidant activity of granules[25]. The freshly prepared 2 ml DPPH methanolic solution (0.1 mM) was incubated with 2 mL of each sample (0.001-1 mg/mL) for 30 min in dark conditions.…”
mentioning
confidence: 99%